The role of silicate surfaces on calcite precipitation kinetics - Stockmann, G.; Wolff-Boenisch, Domenik; Bovet, N.; Gislason, S.; Oelkers, E. (Pergamon, 2014)
The aim of this study is to illuminate how calcite precipitation depends on the identity and structure of the growth substrate. Calcite was precipitated at 25 °C from supersaturated aqueous solutions in the presence of seeds of either calcite or one of six silicate materials: augite, enstatite, labradorite, olivine, basaltic glass and peridotite rock. Calcite saturation was achieved by mixing a CaCl2-rich aqueous solution with a NaHCO3–Na2CO3 aqueous buffer in mixed-flow reactors containing 0.5–2 g of mineral, rock, or glass seeds. This led to an inlet fluid calcite saturation index of 0.6 and a pH equal to 9.1. Although the inlet fluid composition, flow rate, and temperature were identical for all experiments, the onset of calcite precipitation depended on the identity of the seeds present in the reactor. Calcite precipitated instantaneously and at a constant rate in the presence of calcite grains. Calcite precipitated relatively rapidly on labradorite, olivine, enstatite, and peridotite (mainly composed of Mg-olivine) surfaces, but more slowly on augite and basaltic glass.Calcite precipitation rates, however, became independent of substrate identity and mass over time, and all rates approach 10−9.68 ± 0.08 mol/s for ∼10 day long experiments and 10−9.21 ± 0.2 mol/s for ∼70 day long experiments. Scanning Electron Microscope images showed olivine, enstatite and peridotite surfaces to be covered extensively with calcite coatings at the end of the experiments. Less calcite was found on labradorite and augite, and the least on basaltic glass. In all cases, calcite precipitation occurs on the mineral, rock or glass surfaces. Calcite precipitation on these surfaces, however, negligibly affects the dissolution rates of the silicate grains. These results support ultramafic and basalt carbonation as a long-term carbon storage strategy, as calcite readily precipitates on the surfaces of minerals contained in these rocks without inhibiting their dissolution.